IMPROVING MATHEMATICAL PROBLEM-SOLVING ABILITY AND SELF-CONFIDENCE OF HIGH SCHOOL STUDENTS THROUGH CONTEXTUAL LEARNING MODEL - Edy Surya; Feria Andriana Putri; Mukhtar Mukhtar (Journal on Mathematics Education, 2017)
The purposes of this study are: (1) to know if students’ mathematical problem-solving ability taught by contextual learning model is higher than students taught by expository learning, (2) to know if students’ self-confidence taught by contextual learning model is higher than students taught by expository learning, (3) to know if there is interaction between learning model and students’ early mathematical ability to improve students' mathematical problem-solving ability, (4) to know if there is interaction between learning model and students’ early mathematical to improve students' self-confidence. This study is a quasi-experimental research. The population in this study consists of 180 students in grade VIII SMP Muhammadiyah 11 Pangkalan Brandan. Two classes (60 students) are taken as sample. Data were analyzed by two way Anova. The results of this study indicate that (1) students’ capability of solving mathematical problems taught with contextual learning model is higher than students taught by expository, (2) students’ self-confidence taught by contextual learning model is higher than students taught by expository, (3) there is interaction between learning model and students’ early mathematical ability to improve students' mathematical problem-solving ability, (4) there is interaction between learning model and students’ early mathematical to improve students' self-confidence. Keywords: Contextual Learning Model, Mathematical Problem-Solving, Self-Confidence DOI: http://dx.doi.org/10.22342/jme.8.1.3324.85-94